The difference of lower and upper surface hardness ratio between LED-activated hybrid composite resin and nano composite resin - Mona, Deli; Fadil, Mochammad Richata; Andang, Milly Armilia (Universitas Padjadjaran, 2016)
Introduction: Composite polymerization is a polymer molecule formation from monomeric molecules. To obtain good physical and mechanical properties of composite resin restoration, the dental composite resin must have the possibility of an optimal quantity of its monomer converted to the polymer during the polymerization reaction. The type, size, and content of the fillers in the composite are also essential factors in the polymerization process. A hardness test can be used to indirectly measure the hardness ratio of the upper and lower surfaces of the composite material (relative curing degree). The objective of this study was to analyze the differences in the hardness ratio of the upper and lower surface between LED-activated hybrid composite resin and nano composite resin. Methods: Thirty composite resin samples were randomly selected and divided into 2 groups. Group I was the hybrid composite resin group and Group II was the nano composite resin group. Samples were then formed into discs with a diameter of 6mm and a thickness of 2mm and polymerized using LCU LED with a light intensity of 800 mW/cm2 for 20 seconds. After 24 hours, the upper and lower surfaces of each sample were tested for three testing points using Vickers Hardness Tester. The data were then analyzed using the t-test. Results: The hardness ratio between the upper and lower surfaces (relative curing degree) of the hybrid composite resin and nano composite resin was 0.93 and 0.88 consecutively. Conclusion: There is any difference between the upper and lower surface hardness ratio of LED-activated hybrid composite resin and nano composite resin.